2019
DOI: 10.1080/14733285.2019.1699646
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on fire: children’s knowledge and needs after a wildfire disaster in Portugal

Abstract: There is growing international concern about the impact of natural hazards and disasters on children and young people. However, very little research has explored children's views of their wildfire experiences. Using creative methods with two groups of primary school children from an inland area, this qualitative study examines Portuguese children's experiences of a wildfire disaster that affected their community in 2017. An inductive qualitative approach was used to explore the children's interpretations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Post-disaster, it is suggested that education regarding self-protective measures be reinforced. These education programs should be appropriate for children and include parents since infants imitate their behaviors, thus promoting the resilience of the entire community [62].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-disaster, it is suggested that education regarding self-protective measures be reinforced. These education programs should be appropriate for children and include parents since infants imitate their behaviors, thus promoting the resilience of the entire community [62].…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest using tools that, from the education approach in health and self-protection, allowed communities to face risks and prevent such hazards from turning into disasters or rework their experiences once they had occurred. Some of these tools are drawings and children's stories [62], comics or fictional stories [61,63], in-depth interviews and focus groups to determine the level of preparedness and risk perception [60], and also group discussions for community training purposes [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frequently used in child-led participatory initiatives since it can help to stimulate creative thinking about what participants want to achieve and how to achieve it (Molina et al, 2009). Drawing has been used in numerous projects to assist children to articulate their perceptions and knowledge about risk and disaster (Rowland et al, 2017;Ribeiro and Silva, 2019).…”
Section: Art-based Methods: Drawings Storyboards and 3d Modelsmentioning
confidence: 99%
“…However, such initiatives are less pronounced in inland rural areas, where demographic aging and depopulation are severe and isolate young voices. Moreover, young people in such areas suffer directly from the impacts of climate change, such as forest fires, and have concerns that should be mobilized [25,26].…”
Section: Youth Active Citizenship and Environmental Issuesmentioning
confidence: 99%